Changes in Hearing Threshold and Auditory Performance After Cochlear Implantation - Tri Andini; Ajeng Tias Endarti; Sumiati Bedah (FORIKES, 2026)
Hearing impairment is known to interfere with communication ability and may lead to social isolation, emotional distress, depression, and anxiety. Cochlear implant technology represents an effective rehabilitative solution for individuals with severe to profound hearing loss. This study aimed to evaluate the benefits of cochlear implant use through measurements of hearing thresholds and Categorical Auditory Performance II (CAP II) scores before implantation and after six months and one year of device use. A mixed‑methods design with a pre–post group approach was employed, involving a sample of 60 cochlear implant users with more than six months of device experience who met the predetermined eligibility criteria. Data were obtained from the CMS database, questionnaire administration, and interviews with otolaryngologists, audiologists, therapists, and parents of cochlear implant users. Qualitative analysis demonstrated improvements in hearing thresholds and auditory performance following cochlear implantation, which subsequently enhanced verbal communication abilities. These improvements were associated with consistent device use, auditory listening therapy, and adaptation over time. Statistical analyses using Friedman, Wilcoxon, and multiple linear regression tests revealed a significant improvement in hearing thresholds, decreasing from a mean of 104.42 dB before implantation to 48.42 dB after six months and 33.33 dB after one year of use (p < 0.05). CAP II scores also increased substantially, from a mean of 0.57 pre‑implantation to 3.08 at six months and 4.82 at one year. Age, baseline test results, and therapy consistency were identified as influential factors affecting final outcomes. In conclusion, younger age, consistent cochlear implant use, and adherence to auditory verbal or speech therapy were shown to significantly improve hearing ability and auditory performance in individuals with severe to profound hearing impairment.Keywords: cochlear implant; hearing threshold; categorical auditory performance II